Faktor-Faktor yang mempengaruhi Minat Investasi Mahasiswa di Pasar Modal - Gabriella Lioera; Yulius Kurnia Susanto; Dicky Supriatna (Media Bisnis, 2022)
The purpose of this study was to determine the effect of expected return, self efficacy, perceive risk, subjective norms, perceived behavior control, and investment / transaction attitude on investment intention, especially students. The data used in this study are primary data collected from questioner that involve 383 respondents which are active students from various majors in West Jakarta who have an Investment Gallery on their college. Data analysis used multiple linear regression using Statistical Package for Social Science (SPSS). The result shows that expected return, self efficacy, perceive risk, subjective norms, and investment attitude have a significant effect to determine the investment intention. Meanwhile, perceived behavior control doesn’t affect investment intention in students.